2021
DOI: 10.1016/j.ejrad.2020.109416
|View full text |Cite
|
Sign up to set email alerts
|

Can ultrasonography differentiate anastomotic and non-anastomotic biliary strictures after orthotopic liver transplantation- a single‐center experience

Abstract: To evaluate the role of ultrasonography (US) in differentiating anastomotic biliary strictures (AS) and non-anastomotic biliary strictures (NAS) after orthotopic liver transplantation (OLT). Method: This retrospective study included 1259 OLT recipients between 2005− 2018. Seventy-six with anastomotic strictures (AS) and 103 with non-anastomotic strictures (NAS) were analyzed. The reference standard was cholangiography. The sensitivity, specificity, accuracy of US was evaluated. Results: There were significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The ultrasound showed mild bile ducts dilatation containing hyperecogenic material with distinct, smooth and regular luminal contour (Figure 3E). 26 The patients underwent percutaneous biliary placement confirming the diagnosis of anastomotic structure (Figure 3F). He is currently doing well with no evidence of IC 5 months after LT, his last lab values showed bilirubin 1.3 mg/dl with normal transaminases (Figure 2H).…”
Section: Casementioning
confidence: 98%
“…The ultrasound showed mild bile ducts dilatation containing hyperecogenic material with distinct, smooth and regular luminal contour (Figure 3E). 26 The patients underwent percutaneous biliary placement confirming the diagnosis of anastomotic structure (Figure 3F). He is currently doing well with no evidence of IC 5 months after LT, his last lab values showed bilirubin 1.3 mg/dl with normal transaminases (Figure 2H).…”
Section: Casementioning
confidence: 98%
“…The US Characteristics of biliary strictures include biliary dilation, irregularity, discontinuity. Typical US appearance of AS is continuous, regular smooth dilation in the intrahepatic biliary duct, which is distinct from NAS [12]. Abdominal ultrasound has an approximately 100% of sensitivity in testing dilatation and obstruction of intrahepatic bile duct, however it's capacity to detect the masses and strictures is very low [13].…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Some patients are asymptomatic and are identified with elevation of liver enzymes (for example ALT, AST, alkaline phosphatase), rise of bilirubin. 106 Surgical Science dilated central ducts [12].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Liao et al reported that assessment of the bile duct with ultrasound (US) at the hilum showing a diminished or absent bile duct lumen had a sensitivity of 94% and a specificity of 84% for non-anastomotic stricture when compared to cholangiography. Many cases of non-anastomotic stricture and anastomotic strictures are from concomitant HAS [ 29 ].…”
Section: Reviewmentioning
confidence: 99%